Mathematical model of computer system reliability in residual classes - Krasnobayev, Victor; Koshman, Serhii; Nikolsky, Serhii; Kovalchuk, Dmytro (Національний технічний університет "Харківський політехнічний інститут", 2022)
The subject of the article is the construction of a mathematical model of the reliability of a computer system (CS) that operates in a system of residual classes (RNS). This mathematical model is based on the use of structural sliding reservation. The purpose of the article is to increase the reliability of the CS, which operates in the system of residual classes, as well as to calculate and compare the reliability, in terms of the probability of failure-free operation, of the CS in the RNS and the ternary computing system, which operates in the positional binary number system (PBNS). Tasks: to analyze the influence of the number system used on the reliability of the CS; to investigate the properties of the RNS and determine their influence on the structure of the CS in the RNS; build a mathematical model of reliability and, on its basis, perform the calculation and comparative analysis of the reliability of the CS in the RNS and the tripled CS in the PBNS. Research methods: methods of analysis and synthesis of computer systems, number theory, coding theory in RNS, reliability theory. The following results are obtained. The paper shows that the provision of a given level of reliability in the design of the CS using the RNS is due to the presence of various types of redundancy at the same time: structural, informational, temporal, functional and load. In RNS, these types of redundancy can be effectively used to improve the reliability of the CS. The CS in the RNS represents a computational structure that is identical in structure and principle of operation to the sliding structural redundancy model in the PBNS in the case of a loaded (hot) mode of operation of the redundant elements. Proceeding from this, the paper presents a mathematical model of the reliability of the CS in the RNS. In this paper, the calculation and comparative analysis of the reliability of a tripled computing structure in a PBNS with an ideal majority element and a CS in an RNS with an ideal reliability automaton are carried out. Conclusions. As shown by the results of calculations and comparative analysis in some time intervals of operation, the probability of non-failure operation of the CS in the RNS is higher than the probability of non-failure operation of the aircraft in the PBNS with a tripled majority structure. This implies the effective use of the RNS to improve the reliability of the CS.

Предметом статті є побудова математичної моделі надійності комп'ютерної системи (КС), що функціонує у системі залишкових класів (СЗК). Ця математична модель будується на основі використання структурного ковзного резервування. Метою статті є підвищення надійності КС, яка функціонує в системі залишкових класів, а також проведення розрахунку та порівняльного аналізу надійності, за ймовірністю безвідмовної роботи, КС у СЗК та тройованої обчислювальної системи (ОС), яка функціонує у позиційній двійковій системі числення (ПДСЧ). Завдання: провести аналіз впливу системи числення, що використовується, на надійність КС; дослідити властивості СЗК та визначити їх вплив на структуру КС у СЗК; побудувати математичну модель надійності та на її основі провести розрахунок та порівняльний аналіз надійності КС у СЗК та тройованої ОС у ПДСЧ. Методи дослідження: методи аналізу та синтезу комп'ютерних систем, теорія чисел, теорія кодування у СЗК, теорія надійності. Отримано такі результати. У роботі показано, що забезпечення заданого рівня надійності при проектуванні КС з використанням СЗК обумовлено наявністю одночасно різних видів надмірності: структурної, інформаційної, часової, функціональної та навантажувальної. У СЗК зазначені види надмірності можна ефективно використовувати для підвищення надійності КС. КС у СЗК представляє собою обчислювальну структуру, яка ідентична за структурою та принципом функціонування моделі ковзного структурного резервування в ПДСЧ у разі навантаженого (гарячого) режиму функціонування резервних елементів. Виходячи з цього, у роботі представлена математична модель надійності КС у СЗК. У роботі проведено розрахунок та порівняльний аналіз надійності тройованої обчислювальної структури у ПДСЧ з ідеальним мажоритарним елементом та КС у СЗК з ідеальним автоматом надійності. Висновки. Як показали результати розрахунків та порівняльного аналізу в деяких часових інтервалах функціонування, ймовірність безвідмовної роботи КС у СЗК вище за ймовірність безвідмовної роботи ОС у ПДСЧ з тройованою мажоритарною структурою. Це обумовлює ефективне використання СЗК для підвищення надійності КС.
Математична модель надійності комп'ютерної системи у залишкових класах
Keywords: number system; residual class system; positional binary number system; mathematical model; reliability of computer systems and components; система числення; система залишкових класів; позиційна двійкова система числення; математична модель; надійність комп'ютерних систем та компонентів